1973
DOI: 10.1161/01.res.33.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Receptor Activity of Rabbit Aorta

Abstract: IV-ethylmaleimide (NEM), an alkylating agent that covalently binds sulfhydryl groups, and dithiothreitol (DTT, Cleland's reagent), which reduces disulfide bridges to sulfhydryl groups, affected drug-induced contractions of rabbit aorta. NEM depressed aortic responses to potassium chloride (KC1), norepinephrine, serotonin, histamine, and angiotensin II. This action was attributed to an interaction of NEM with sulfhydryl groups vital to either the membrane function or the contractile apparatus. DTT had minimal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…When we compared the effect of DTT and NEM on the histamine H~-receptor binding site in beef aortic membranes with the effects of the two reagents on the histamine-induced contractions of isolated rabbit aorta [1,2], we obtained a good correlation between the radioligand binding and pharmacological data. DTT, similarly to the results of the binding experiments (Fig.…”
Section: Figurementioning
confidence: 91%
See 2 more Smart Citations
“…When we compared the effect of DTT and NEM on the histamine H~-receptor binding site in beef aortic membranes with the effects of the two reagents on the histamine-induced contractions of isolated rabbit aorta [1,2], we obtained a good correlation between the radioligand binding and pharmacological data. DTT, similarly to the results of the binding experiments (Fig.…”
Section: Figurementioning
confidence: 91%
“…In our previous experiments, we showed that DTT and NEM altered the contractile responses, induced by histamine, in the rabbit aortic tissue [1,2]. This alteration in the receptor activity lead us to investigate, at the molecular level, the influence of the same reagents on the histamine Hi-receptor binding sites.…”
Section: I5]mentioning
confidence: 96%
See 1 more Smart Citation
“…That lignocaine relaxes or modifies vascular responses of rat aorta and sheep carotid artery has been reported (Fleisch & Titus, 1973;Jacobs & Keatinge, 1974) Passive leg raising causes a reflex vasodilatation of forearm vasculature owing to stimulation of low-pressure receptors in the intrathoracic vascular bed (Roddie, Shepherd & Whelan, 1957). The anti-gravity suit (G suit) also causes redistribution of blood volume to the thorax by the application of pneumatic pressure to the legs and lower abdomen.…”
Section: Pmentioning
confidence: 99%
“…After perfusion of isolated vascular smooth muscles with this agent there is a potentiation of the vasoconstrictor responses to histamine (Fleisch, Krzan & Titus, 1973;Carroll & Glover, 1977). If this potentiation of histamine by dithiothreitol is due to reduction of a disulphide linkage in a histamine receptor (Fleisch et al 1973) it is possible that such a change in a receptor-linked protein would activate that receptor. In isolated rabbit-ear arteries a large and prolonged contraction follows perfusion with dithiothreitol (Allen & Deering, 1976).…”
Section: P Proceedings Of Thementioning
confidence: 99%